The Effect of the Ownership Structure and Characteristics of The Board on Stock Market Liquidity in Manufacturing Companies in the Non-Cyclicals Consumer Goods Industry Sector on The Indonesia Stock Exchange - Dita Noviany; Henny Setyo Lestari (International Journal of Education, Information Technology, and Others, 2022)
Stock market liquidity attracts the attention of researchers especially in emerging markets because market liquidity helps to allocate efficient financial resources. Increased stock market liquidity has an effect on the efficiency of stock valuations, and therefore can help increase the value of the company. Therefore, this study was conducted to determine whether the ownership structure, board characteristics had an effect on the liquidity of the stock market. The independent variables are the ownership structure with institutional investor and managerial ownership proxies and the characterization of the board with board size proxies and board independence. The depen variable is the liquidity of the stock market. There are three control variables in this study, namely firm size, firm age and return volatility. This study collected data from 34 manufacturing companies in the non-cyclicals consumer goods industry sector listed on the Indonesia Stock Exchange within a period of 5 years (2017-2021) and used a multiple regression model for testing. The findings of this study show that institutional investors, managerial ownership, return volatility do not have a significant effect on stock market liquidity. Meanwhile, board size, board independence, firm size, firm age have a significant effect on stock market liquidity. The results of this study can be used to present a successful model for manufacturing companies in Indonesia to concentrate more on the ownership structure. board characteristics in stock market liquidity. All of these studies used LR as a measurement of stock market liquidity. In the novelty of this study, it eliminates one of the independent variables so that the measurement can be distinguished from previous studies